2021
DOI: 10.3390/ijms22094823
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Outer Membrane Vesicles and Extracellular Vesicles from Helicobacter pylori-Infected Cells in Gastric Disease Development

Abstract: Extracellular vesicles (EVs) are cell-derived vesicles important in intercellular communication that play an essential role in host-pathogen interactions, spreading pathogen-derived as well as host-derived molecules during infection. Pathogens can induce changes in the composition of EVs derived from the infected cells and use them to manipulate their microenvironment and, for instance, modulate innate and adaptive inflammatory immune responses, both in a stimulatory or suppressive manner. Gastric cancer is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 186 publications
(289 reference statements)
1
37
0
Order By: Relevance
“…H. pylori peptidoglycan delivered into host cells by the T4SS is recognized by epithelial cells via Nod1 [72], leading to NF-κB activation and the production of β-defensin and type I IFNs from Nod1-activated gastric epithelial cells [73][74][75]. H. pylori can secrete outer membrane vesicles (OMVs) separated from the bacterial outer membrane [76]. OMVs containing peptidoglycan enter epithelial cells at cholesterol-rich lipid rafts and induce NOD1-dependent response [77].…”
Section: Pamps Derived From H Pylori Inducingmentioning
confidence: 99%
“…H. pylori peptidoglycan delivered into host cells by the T4SS is recognized by epithelial cells via Nod1 [72], leading to NF-κB activation and the production of β-defensin and type I IFNs from Nod1-activated gastric epithelial cells [73][74][75]. H. pylori can secrete outer membrane vesicles (OMVs) separated from the bacterial outer membrane [76]. OMVs containing peptidoglycan enter epithelial cells at cholesterol-rich lipid rafts and induce NOD1-dependent response [77].…”
Section: Pamps Derived From H Pylori Inducingmentioning
confidence: 99%
“…About a hundred different proteins are found, including several H. pylori virulence factors, such as VacA, CogA, urease, and catalase (KatA). 75,89,90 H. pylori OMVs carry VacA and can deliver the active toxin to epithelial cells to stimulate proliferation, IL-8 secretion, vacuolation, and cell apoptosis. 91,92 KatA is an antioxidant enzyme and enriched in the surface of OMVs.…”
Section: Role Of Omvs In Helicobacter Pylori Infectionmentioning
confidence: 99%
“…Since EVs are a nanocarrier of molecules from pathogens and pathogen-infected cells, González and colleagues proposed a hypothesis that EVs released from H. pylori-infected gastric epithelial cells can enter the blood and reach other tissues, resulting in extragastric diseases. 75 In particular, the EVs from H. pylori-infected cells may encapsulate the H. pylori virulence factors and AS-associated microRNAs (miRNAs).…”
Section: Extracellular Vesicles (Evs) From Helicobacter Pylori-infect...mentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should determine and characterize the sRNAs present in OMV's from Fusobacterium nucleatum, to establish possible biological effects in hosts. Importantly, it was suggested that OMVs from H pylori could be implicated in gastric cancer development [119]; however, it is not known the role of OMVs from Fusobacterium nucleatum in the context of cancer. Thus, signaling by sRNA packed in OMVs and transported out of bacteria associated with cancer must be addressed, since knowledge in this area is lacking and presents potential clinical applications as delivering vectors combined with possible small RNA based therapy.…”
Section: Importance Of the Identification And Characterization Of Small Rnas In Bacteriamentioning
confidence: 99%